Cellulose synthesis - central components and their evolutionary relationships - Lampugnani, Edwin R. (2021)
Cellulose is an essential morphogenic polysaccharide that is central to the stability of plant cell walls and provides an important raw material for a range of plant-based fiber and fuel industries. The past decade has seen a substantial rise in the identification of cellulose synthesis-related components and in our understanding of how these components function. Much of this research has been conducted in Arabidopsis thaliana (arabidopsis); however, it has become increasingly evident that many of the components and their functions are conserved. We provide here an overview of cellulose synthesis 'core' components. The evolution and coexpression patterns of these components provide important insight into how cellulose synthesis evolved and the potential for the components to work as functional units during cellulose production.